Dog walking: Doing class and undoing anthropocentrism - Mhlongo, Nkululeko Benedict; Canham, Hugo (PINS-Psychology in Society, 2021)
Beginning with anecdotal accounts about the aspirations of black middle-class people, with dog walking as the point of entry, this study sought to understand the meanings attached to dog walking from the perspectives of ten middle-class black people who walk their dogs. Applying discourse analysis to interview data we found that dog walking is a habituated class performance. While some disavowed the idea of dog walking as a performance of middle classness, we suggest that performativity is always at play in the social practice of dog walking. Secondly, the study found that we should nuance our understandings of black middle-class people in order to recognize the continuities and discontinuities with the black working class. Finally, the study found that black people relate to their dogs in ways that disturb the colonial artifact of the human–animal binary. We observe that dog walking and orders of care exceed utilitarian needs and suggest cosmological and psychological relatedness that undo deeply rooted anthropocentrism in the social sciences. Ultimately, through the lens of class, the study suggests that the human is less distinct from the animal than the Chain of Being would have us believe.